Nucleophilic dearomatization of 4-aza-6-nitrobenzofuroxan by CH acids in the synthesis of pharmacology-oriented compounds - Starosotnikov, Alexey M.; Shkaev, Dmitry V.; Bastrakov, Maxim A.; Fedyanin, Ivan V.; Shevelev, Svyatoslav A.; Dalinger, Igor L. (Beilstein Journal of Organic Chemistry, 2017)
4-Aza-6-nitrobenzofuroxan (ANBF) reacts with 1,3-dicarbonyl compounds and other CH acids to give carbon-bonded 1,4-adducts – 1,4-dihydropyridines fused with furoxan ring. In the case of most acidic β-diketones, which exist mainly in the enol form in polar solvents, the reactions proceed in the absence of any added base emphasizing the highly electrophilic character of ANBF. The resulting compounds combine in one molecule NO-donor furoxan ring along with a pharmacologically important 1,4-dihydropyridine fragment and therefore can be considered as prospective platforms for the design of pharmacology-oriented heterocyclic systems.
Keywords: CH acids; dearomatization; 1,4-dihydropyridines; furoxans; nitropyridines